Novel Golden Lipid Nanoparticles with Small Interference Ribonucleic Acid for Substrate Reduction Therapy in Fabry Disease - Marina Beraza-Millor; Julen Rodríguez-Castejón; Jonatan Miranda; Ana del Pozo-Rodríguez; Alicia Rodríguez-Gascón; María Ángeles Solinís (MDPI AG, 2023)
Substrate reduction therapy (SRT) has been proposed as a new gene therapy for Fabry disease (FD) to prevent the formation of globotriaosylceramide (Gb3). Nanomedicines containing different siRNA targeted to Gb3 synthase (Gb3S) were designed. Formulation factors, such as the composition, solid lipid nanoparticles (SLNs) preparation method and the incorporation of different ligands, such as gold nanoparticles (GNs), protamine (P) and polysaccharides, were evaluated. The new siRNA-golden LNPs were efficiently internalized in an FD cell model (IMFE-1), with GNs detected in the cytoplasm and in the nucleus. Silencing efficacy (measured by RT-qPCR) depended on the final composition and method of preparation, with silencing rates up to 90% (expressed as the reduction in Gb3S-mRNA). GNs conferred a higher system efficacy and stability without compromising cell viability and hemocompatibility. Immunocytochemistry assays confirmed Gb3S silencing for at least 15 days with the most effective formulations. Overall, these results highlight the potential of the new siRNA-golden LNP system as a promising nanomedicine to address FD by specific SRT.